The New Silk Road – Economic Belt Policy: The Great Chance for the Rejuvenation of Europe - K., Kondybayeva S.; A, Celetti D.; A., Yerkin N. (Farabi Journal of Social Sciences, 2019)
Abstract. The paper presents that Europe is now being shaken by a series of crises such as the Greek crisis, the refugee catastrophe and the imminent turbulence of the Trans – Atlantic financial sector. In that context, the perspective of the OBOR / New Silk Road is the only positive way to be able to find a form of cooperation, which will allow these problems to be overcome on a higher level. It also states that when we talk about the «New Silk Road becomes the World Land Bridge» as a vision for the future, we should see it as a synonym not only for a new just economic order, and emphatically as the basis for a peace order for 20th century, based on completely different economic and scientific principles than the previous system of globalization, but also for a new paradigm concerning the identity of the human species as the only creative species known so far in the universe. Key words: OBOR, Refugee Catastrophe, Euro crisis, the World Land – bridge.